2020
DOI: 10.3390/v12060606
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Retrovirus (Gunnison’s Prairie Dog Retrovirus) Associated With Thymic Lymphoma in Gunnison’s Prairie Dogs in Colorado, USA

Abstract: As part of research and wildlife disease surveillance efforts, we performed necropsy examinations of 125 free-ranging (n = 114) and captive (n = 11) prairie dogs in Colorado from 2009 to 2017. From these cases, we identified three cases of thymic lymphoma in free-ranging Gunnison’s prairie dogs (Cynomys gunnisoni), and we identified a novel retroviral sequence associated with these tumors. The viral sequence is 7700 nucleotides in length and exhibits a genetic organization that is consistent with the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, lesions were remarkably similar in distribution and severity, which could indicate a viral etiology. Oncogenic viruses, specifically those of the retroviral lineage, such as the Koala Retrovirus and Gunnison's Prairie Dog Retrovirus are associated with lymphoid neoplasia in wildlife in Australia and elsewhere [43,44]. As males were slightly overrepresented with lymphoid neoplasia in this study, it is less likely that a viral entity is involved although it might be worth exploring this hypothesis in future studies.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, lesions were remarkably similar in distribution and severity, which could indicate a viral etiology. Oncogenic viruses, specifically those of the retroviral lineage, such as the Koala Retrovirus and Gunnison's Prairie Dog Retrovirus are associated with lymphoid neoplasia in wildlife in Australia and elsewhere [43,44]. As males were slightly overrepresented with lymphoid neoplasia in this study, it is less likely that a viral entity is involved although it might be worth exploring this hypothesis in future studies.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, lesions were remarkably similar in distribution and severity, which could indicate a viral etiology. Oncogenic viruses, specifically those of the retroviral lineage, such as the Koala Retrovirus and Gunnison's Prairie Dog Retrovirus are associated with lymphoid neoplasia in wildlife in Australia and elsewhere [50,51]. This hypothesis might be worth exploring in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Butler et al [12] successfully identified a novel type D beta-retrovirus Gunnison's prairie dog retrovirus (GPDRV) linked with three cases of thymic lymphoma, a type of blood cancer, in free-ranging Gunnison's prairie dogs. The authors demonstrated that infection with GPDRV can lead to developing thymic lymphoma in Gunnison's prairie dogs.…”
mentioning
confidence: 99%